Ecological restoration strategies associated with reforestations of Pinus cembroides Zucc., in the Parque Nacional Cumbres de Monterrey - Sandoval-García, Rufino; Jiménez-Pérez, Javier; Yerena-Yamallel, José Israel; Aguirre-Calderón, Oscar Alberto; Alanís-Rodríguez, Eduardo; Gómez-Meza, Marco Vinicio (Instituto de Ecología, A.C., 2022)
Most reforestations in Mexico have a low survival rate and are abandoned after their establishment; therefore, they cannot be considered as a real alternative solution, because a proper ecological restoration process requires that the activities are based on the needs of the ecosystem, have a design and implementation of strategies, as well as an evaluation and monitoring program. The present study aims to analyze the survival and growth of a reforestation of Pinus cembroides Zucc., in combination with different ecological restoration strategies in the Parque Nacional Cumbres de Monterrey. Results indicate that strategies of nucleation, association of functional groups, and generation of microclimatic conditions in combination with reforestation increase the percentage of survival up to 92%, improve the infiltration capacity, and reduce water stress. The fog-trapping mesh had an average condensation of 0.8 l/m2/day of fog and dew, as well as a 70% reduction in light intensity. The hydrogel requires constant hydration; therefore, its effectiveness is reduced in areas of low precipitation. The translocation of soils improves infiltration capacity and the association of Anderson functional groups, allowing a symbiotic association that improves the fixation of N and other macronutrients for plants.